FRIB helium refrigeration system commissioning and performance test results. Issue 1 (March 2020) - Knudsen, P; Ganni, V; Hasan, N; Wright, M; Casagrande, F; Vargas, G; Joseph, N
Abstract: At its maximum capacity condition, the 4.5 K refrigerator system for the Facility for Rare Isotope Beams (FRIB) accelerator supports a 180 g/s 30 K 1.16 bar cold compressor return flow, a 14 g/s 4.5 K liquefaction load, a 4 kW 4.5 K refrigeration load, and a 20 kW 35-55 K shield load. Five additional design conditions, ranging from liquefaction to refrigeration and a stand-by/reduced load state, were specified for the sizing and selection of its components. The cold box system is comprised of a 300-60 K vertical cold box that incorporates a liquid nitrogen pre-cooler and a 60-4.5 K horizontal cold box housing seven turbines that are configured in four expansion stages including one Joule-Thompson expander. This cold box system, operates using the Ganni-Floating pressure process, automatically adjusting to the linear accelerator (Linac) load with the cold box supply (and compressor discharge) pressure varying from 6 to 21 bar, without introducing additional (artificial) loads or throttling turbine inlet valves (or other exergy loss mechanisms), and with minimal liquid nitrogen usage. This paper will briefly review the salient 4.5 K system design features and discuss the recent commissioning results.